2011
DOI: 10.1002/dev.20559
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that angiogenesis lags behind neuron and astrocyte growth in experience‐dependent plasticity

Abstract: Bill Greenough's work on the cell biology of information storage suggests that we cannot understand the mechanism of long-term memory without understanding the series of cellular transactions that drive coordinated structural changes in neurons, glia, and blood vessels. Here, we show that after 4 days of differential housing, neuropil of EC cortex has expanded significantly, but the vasculature has not, resulting in a dilution of the blood supply. Significant growth of neurons and astrocytes has been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 137 publications
(125 reference statements)
0
4
0
1
Order By: Relevance
“…The specific reasons for changes in plasticity with age may stem from metabolic or transcriptional changes associated with ageing, such as a decline in growth hormones like IGF‐1 or BDNF (Barzilai, Huffman, Muzumdar, & Bartke, ; Kirk I Erickson et al, ) or with changes in angiogenesis. Indeed, it has been suggested that the neuronal capacity for plasticity may be constrained by the rate of vascularization (Wallace, Withers, Farnand, Lobingier, & McCleery, ). However, further work is needed to fully elucidate the role of these factors in exercise‐induced changes in hippocampal plasticity and neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The specific reasons for changes in plasticity with age may stem from metabolic or transcriptional changes associated with ageing, such as a decline in growth hormones like IGF‐1 or BDNF (Barzilai, Huffman, Muzumdar, & Bartke, ; Kirk I Erickson et al, ) or with changes in angiogenesis. Indeed, it has been suggested that the neuronal capacity for plasticity may be constrained by the rate of vascularization (Wallace, Withers, Farnand, Lobingier, & McCleery, ). However, further work is needed to fully elucidate the role of these factors in exercise‐induced changes in hippocampal plasticity and neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Как показано в многочисленных исследованиях у животных, обогащение среды оказывает на головной мозг широкий спектр воздействий, включая повышение уровня нейротрофических факторов и повышение экспрессии генов, контролирующих нейронную сигнализацию и синтез белка [52]. Обогащение среды и обучение новым навыкам увеличивает скопление отростков нейронов (нейропиль) в коре [64] и приводит к структурным изменениям в зубчатой извилине, поясной коре и мозолистом теле [6].…”
Section: реактивация нейропластичности и обогащение средыunclassified
“…The cortex of rodents exposed to enriched environments during young adulthood show increased levels of neurotrophic factors and higher expression of genes controlling neuronal signalling/growth, RNA, and protein synthesis (Rampon et al 2000a ; Torasdotter et al 1998 , 1996 ). Also, enriched environments and new learning have been shown to increase neuropil in the cortex (Wallace et al 2011 ), and result in structural changes in the dentate gyrus, cingulate cortex and corpus callosum (Blumenfeld-Katzir et al 2011 ). These animal findings support the use of this apparently benign behavioural approach to enhance brain health/function in TBI.…”
Section: Environmental Enrichment Provides Opportunities For Intervenmentioning
confidence: 99%